1996
DOI: 10.1021/jm960063l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Phorboid 20-Homovanillates:  Discovery of a Class of Ligands Binding to the Vanilloid (Capsaicin) Receptor with Different Degrees of Cooperativity

Abstract: A number of phorboid 20-homovanillates were prepared by condensation of phorbol 12,13-diesters and 12-dehydrophorbol 13-esters with Mem-homovanillic acid followed by removal of the protecting group with SnCl4 in THF. These compounds were evaluated for their ability to inhibit [3H]resiniferatoxin (RTX) binding to rat spinal cord membranes. Compounds bearing a lipophilic ester group on ring C were considerably active, but a surprising tolerance of the vanilloid receptor toward the location and the orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…Piperine has been reported to be pungent but not to desensitize (Liu and Simon, 1996). Several capsaicin analogs with a phorbol ester as a C region were inactive for modulating thermoregulation, although they were potent for neurogenic inflammation Appendino et al, 1996). The loss of the range of vanilloid responses in mice null for VR1 argues against the otherwise attractive model that multiple genes for the vanilloid receptor exist (Caterina et al, 2000;Davis et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Piperine has been reported to be pungent but not to desensitize (Liu and Simon, 1996). Several capsaicin analogs with a phorbol ester as a C region were inactive for modulating thermoregulation, although they were potent for neurogenic inflammation Appendino et al, 1996). The loss of the range of vanilloid responses in mice null for VR1 argues against the otherwise attractive model that multiple genes for the vanilloid receptor exist (Caterina et al, 2000;Davis et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[12] The new location of the bridge forces ring C into a boat-like conformation, and the closure of a semiacetal ring with the 9-hydroxy group of 6a further contributes to the overall mimicry of the conformation of RTX. A precursor for the α-ketol rearrangement (4b) was prepared from 13-acetylphorbol 20-trityl ether (3c) [9] by PCC oxidation of the secondary C-12 hydroxy group. Surprisingly, the rearrangement of 4b took different courses in methanol and in ethanol.…”
Section: Ring C Modificationsmentioning
confidence: 99%
“…The regiochemistry of esterification was verified by NOE experiments carried out on the final 20-homovanillates 5d and 6d, obtained by a previously established procedure (removal of the trityl group with HClO 4 , esterification with Mem-protected homovanillic acid, and SnCl 4 -mediated deprotection of the phenolic hydroxy group). [9] The NOE experiments showed that in both 5d and 6d the phenylacetyl group was bound to the hydroxy group at C-12 [NOEs between the phenyl protons and the α-oriented methyl groups (C-18 and C-16)]. Alternative locations for the phenylacetyl residue, namely at the C-9 hydroxy group for the phorbobutanone homovanillate (5d) or at the semiacetal oxygen for the phorboisobutyl ketone homovanillate (6d), would have involved lack of correlation with the methyl group (C-16) (esterification of the 10-hydroxy group of 5d) or with the methyl group (C-18) (esterification of the semiacetalic hydroxy group of 6d).…”
Section: Ring C Modificationsmentioning
confidence: 99%
See 2 more Smart Citations